Stimuli-responsive surfaces for biomedical applications - Costa, Rui R. (2013)
[Excerpt] Surface engineering is a field of expertise dealing with the modification and improvement of interfaces. In conventional medicine, the surface properties of an implantable device are regarded with the utmost importance since the first contact with the organism is mediated by the interface with the organism. This interaction is what drives the subsequent tissue and cellular events, including protein adsorption, cell adhesion, and inflammatory response.[1-3]